Decreased hypertrophic differentiation accompanies enhanced matrix formation in co-cultures of outer meniscus cells with bone marrow mesenchymal stromal cells - Saliken, David JJ (BioMed Central, 2012)
INTRODUCTION: The main objective of this study was to determine whether meniscus cells from the outer (MCO) and inner (MCI) regions of the meniscus interact similarly to or differently with mesenchymal stromal stem cells (MSCs). Previous study had shown that co-culture of meniscus cells with bone marrow-derived MSCs result in enhanced matrix formation relative to mono-cultures of meniscus cells and MSCs. However, the study did not examine if cells from the different regions of the meniscus interacted similarly to or differently with MSCs. METHODS: Human menisci were harvested from four patients undergoing total knee replacements. Tissue from the outer and inner regions represented pieces taken from one third and two thirds of the radial distance of the meniscus, respectively. Meniscus cells were released from the menisci after collagenase treatment. Bone marrow MSCs were obtained from the iliac crest of two patients after plastic adherence and in vitro culture until passage 2. Primary meniscus cells from the outer (MCO) or inner (MCI) regions of the meniscus were co-cultured with MSCs in three-dimensional (3D) pellet cultures at 1:3 ratio, respectively, for 3 weeks in the presence of serum-free chondrogenic medium containing TGF-β1. Mono-cultures of MCO, MCI and MSCs served as experimental control groups. The tissue formed after 3 weeks was assessed biochemically, histochemically and by quantitative RT-PCR. RESULTS: Co-culture of inner (MCI) or outer (MCO) meniscus cells with MSCs resulted in neo-tissue with increased (up to 2.2-fold) proteoglycan (GAG) matrix content relative to tissues formed from mono-cultures of MSCs, MCI and MCO. Co-cultures of MCI or MCO with MSCs produced the same amount of matrix in the tissue formed. However, the expression level of aggrecan was highest in mono-cultures of MSCs but similar in the other four groups. The DNA content of the tissues from co-cultured cells was not statistically different from tissues formed from mono-cultures of MSCs, MCI and MCO. The expression of collagen I (COL1A2) mRNA increased in co-cultured cells relative to mono-cultures of MCO and MCI but not compared to MSC mono-cultures. Collagen II (COL2A1) mRNA expression increased significantly in co-cultures of both MCO and MCI with MSCs compared to their own controls (mono-cultures of MCO and MCI respectively) but only the co-cultures of MCO:MSCs were significantly increased compared to MSC control mono-cultures. Increased collagen II protein expression was visible by collagen II immuno-histochemistry. The mRNA expression level of Sox9 was similar in all pellet cultures. The expression of collagen × (COL10A1) mRNA was 2-fold higher in co-cultures of MCI:MSCs relative to co-cultures of MCO:MSCs. Additionally, other hypertrophic genes, MMP-13 and Indian Hedgehog (IHh), were highly expressed by 4-fold and 18-fold, respectively, in co-cultures of MCI:MSCs relative to co-cultures of MCO:MSCs. CONCLUSIONS: Co-culture of primary MCI or MCO with MSCs resulted in enhanced matrix formation. MCI and MCO increased matrix formation similarly after co-culture with MSCs. However, MCO was more potent than MCI in suppressing hypertrophic differentiation of MSCs. These findings suggest that meniscus cells from the outer-vascular regions of the meniscus can be supplemented with MSCs in order to engineer functional grafts to reconstruct inner-avascular meniscus.